Conflits d’usage de l’espace au Rondônia (Amazonie brésilienne) - Martine Droulers; François-Michel Le Tourneau; Luciana Machado (Cybergeo)
The state of Rondônia, in the Brazilian Amazon, is a region where conflicts between the old politics of agrarian land colonization and the new obligations of environment preservation can be witnessed. Indeed, this region, which has seen a wide effort from the Brazilian state to implant small scale farming in the middle of the rainforest, is today within a huge internationally funded zoning program, officially aiming at a better environment preservation. This paper describes relations and conflicts between the actors involved in land occupation. We take a closer look at this issue by analyzing the Ariquémes/Buritis region case, which allows us to encompass in one glance previously and newly occupied zones. Using a GIS, we can point out discrepancies between the political discourse about the region and the reality, as shown by satellite images. We thus produce cartographic synthesis, highlighting the dynamics at stake in this region.